PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN FRANCHISE O’CHICKEN DI KECAMATAN BUKITRAYA KOTA PEKANBARU - Azizah Azmi; Yusmini Yusmini; Evy Maharani (Indonesian Journal of Agricultural Economics, 2019)
This study aims was analyze the marketing mix that influences consumer purchasing decisions O’Chicken, Analyzing the relationship between the marketing mix of consumer purchasing decisions O’Chicken. This research using purposive sampling method with the respondents of the study amounted to 50 respondents who have aged > 15 years, shop at O’Chicken more than 1 times. The data were analyzed using Likert scale, validity test, reliability test and Cartesian diagram. The results showed that of the five marketing mix variables, all of which are in the category of "influential". Cartesian diagram analysis shows consumer evaluation based on the level of interest expected by consumers. Quadrant I there is no variable in it, quadrant II which included in that is product and price variable is factor which is considered important for consumer, quadrant III there is promotion variable and location that felt less important for consumer, quadrant IV variable which included in that is service considered exaggerated for consumer but very satisfying. It is recommended that the O'Chicken should improve the marketing mix such as: product, price, place, promotion, service, and evaluate consumer expectation in accordance with the level of importance that has been analyzed using katesius diagram so that consumers will continue to shop and not switch to the fried chicken brand competitors